2016
DOI: 10.1002/qj.2774
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the impact of IASI observations through an updated observation‐error covariance matrix

Abstract: This article investigates the use of an updated observation-error covariance matrix for the Infrared Atmospheric Sounding Interferometer (IASI) in the European Centre for Medium-Range Weather Forecasts (ECMWF) system. The new observation-error covariance matrix is based on observation-space diagnostics and includes interchannel error correlations, but also assigns significantly altered error standard deviations. The update is investigated in detail in assimilation experiments, including an assessment of the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
178
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(193 citation statements)
references
References 24 publications
(53 reference statements)
8
178
2
Order By: Relevance
“…Correlated observation error statistics have been diagnosed for certain observation types (e.g., see other works [20][21][22][23][24][25][26][27] ), although there are problems associated with their use. In particular, the methods used to diagnose observation error covariance matrices are imperfect, and the quality of these estimates is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Correlated observation error statistics have been diagnosed for certain observation types (e.g., see other works [20][21][22][23][24][25][26][27] ), although there are problems associated with their use. In particular, the methods used to diagnose observation error covariance matrices are imperfect, and the quality of these estimates is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant research investigating spatial correlations, 20,23,27,51 but much current work concerns the practical implementation of interchannel correlations for satellite observations. 3,6,9,21,22,26 Although the theory presented in Section 3 applies directly to the case of interchannel correlations, it would be of interest to extend our numerical testing to the interchannel covariance case. In particular, practical experiments have revealed that the minimum eigenvalue of the observation error correlation matrix is important for the conditioning of the Hessian in the case of interchannel correlations, 3,9 which coincides with the theoretical and experimental results presented in this work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, prognostic error models of the data are a functional requirement, and these models need to undergo validation as well. Wherever possible error covariances should also be provided (Bormann et al, 2016), which include correlations of errors among different aerosol products from a given sensor, correlations of errors in time (especially for re-trievals from geostationary satellites), and correlations of errors in space (e.g., due to the similarity in surface properties or viewing geometries). Additionally, other information is deemed necessary for the correct assimilation of the observations, such as averaging kernels for chemical species.…”
Section: Uncertaintymentioning
confidence: 99%